Clinical and radiographic outcomes of the use of capping materials in vital pulp therapy of human primary teeth - Lourenço Neto, Natalino; Moretti, Ana Beatriz Silveira; Sakai, Vivien Thiemy; Machado, Maria Aparecida Andrade Moreira; Abdo, Ruy César Camargo; Oliveira, Thais Marchini (Brazilian Dental Science, 2015)
Objective: The aim of this study was to compare the clinical and radiographic outcomes of Calcium Hydroxide (CH), Calcium Hydroxide preceded by corticosteroid/antibiotic solution (O+CH) and diluted formocresol (FC) in the vital pulp therapy of human primary teeth. Material and methods: Forty-five mandibular primary molars of children aged between 5-9 years were randomly assigned in the three study groups, FC, CH and O+CH and received conventional pulpotomy treatment. Clinical and radiographic follow-up was made at 3, 6 and 12-months. Results: No sign of clinical failure was observed in the three study groups during all the periods of evaluation. Radiographic analysis showed a total of six cases of internal root resorption in CH and O+CH groups after the 12 months follow-up, with statistically significant difference as compared with FC group. FC group did not show hard tissue barrier formation, that was observed in CH and O+CH groups in all the follow-up periods. Conclusion: All employed materials showed acceptable clinical and radiographic success rates. The results showed that the use of an anti-inflammatory solution prior the dressing material has therapeutic properties that help with pulpal healing. Continued clinical investigations using these medicaments as vital pulpotomy treatment in primary molars are recommended.